Osteolysis following PE Wear of a Hastings Head on a Monoblock Hip Stem - Sarah Fischer; Valerie Polster; Miriam Ruhr; Robert Hube; Michael M. Morlock (Case Reports in Orthopedics)
We report a case of extended osteolysis, requiring a third revision of the left hip in an 85-year-old man 46 years after index operation. Major polyethylene (PE) wear occurred due to a missmatched combination of a bipolar Hastings head with a PE liner and head damage of the originally maintained stem. This case demonstrates that bipolar heads should not be used with PE cup liners since the respective bearing diameters cannot be guaranteed to match due to missing specifications. Furthermore, putting a Hastings head on an already damaged head of the stem should be omitted and rather the stem should initially be revised.